The electrical properties of nickel (II) phthalocyanine and phenyl-C61-butyric-acid-methyl ester doped nematic liquid crystals under laser light - Ozdemir, Z. Guven; Canli, N. Yilmaz; Yilmaz, Omer; Kirsoy, Ahmet; Okutan, Mustafa; Koysal, Oguz (WILEY-BLACKWELL, 2015)
Because of increasing attention of technological device applications of liquid crystals (LCs), determination of their electrical properties becomes important. In this work, experimental optimization for concentration and laser power effects on nematic LC's voltage-controlled negative resistance behavior has been studied co-usage of nickel (II) phthalocyanine (NiPc) and phenyl-C-61-butyric-acid-methyl ester (PCBM) polymer in nematic liquid crystal (E63). NiPc concentration has been arranged to be between percentages changing from 1 to 5 wt%, whereas a 1 wt% of PCBM has been used in E63 LC. The LC cells have been exposed to 632-nm laser illumination with power of 0-100 mW, and the influence of laser illumination on current-voltage (I-V) characteristics has also been examined. According to I-V measurements of the LC composites under laser illumination, an increase in current has been observed because of dispersal agents of NiPc and PCBM. The possible reason behind this result can be the increase of the impurity ion in E63 under laser illumination. Ionic charge carriers can move freely in the volume of the LC structure and hence conductivity increases. The value of the current increases for NiPc doped E63 in the dark, and it increases further to a higher value under photo-irradiation because of the ionic charges caused by photo-excited electrons from NiPc to LC medium. The higher increase in conductivity has been observed to more efficient free-charge carrier collection provided by 5 wt% NiPc and 1 wt% PCBM doped in LC hybrid medium under laser irradiation. Copyright (C) 2015 John Wiley & Sons, Ltd.
Keywords: nematic liquid crystal; phenyl-C-61-butyric-acid-methyl ester; nickel (II) phthalocyanine; CONDUCTION; MEMORY; PHASES; Polymer Science